Young Teenagers’ Views Regarding Residential Care in Portugal and Spain: A Qualitative Study - Montserrat, Carme (2021)
Research on residential care has been well established in the literature. Nonetheless, research drawing from the actual experiences of adolescents is relatively scarce. A qualitative study was designed highlighting the voices of children, analysing their fostering experience, interpersonal relationships, their participation in daily decisions, and future aspirations. The sample included 33 early adolescents in residential care aged 12–14 in Portugal (n = 17) and Spain (n = 16). Results showed that there was agreement in terms of the importance given to education, their satisfaction with the material conditions of residential centre, and their dissatisfaction concerning matters of individuality, autonomy, participation, and socialization.